Should gastric aspirate be discarded or retained when gastric residual volume is removed from gastric tubes? - Williams, Teresa; Leslie, Gavin (Elsevier Inc, 2010)
Summary: Nursing care of patients with enteral feeding tubes is common in the intensive care unit but the evidence that surrounds the practice is limited. Recent research by Juve-Udina and colleagues (2010) "To return or to discard? Randomised trial on gastric residual volume management" compares two methods of managing gastric residual volume. This critique provides a brief summary of their research and critically appraises the paper. The implications for nursing practice are discussed.